Modelación de demanda de transporte urbano en Costa Rica, de Emme a TransCAD - Castro Rodríguez, Leonardo (2025)
The Modelo de Demanda de Transporte Urbano de la Gran Área Metropolitana en Plataforma TransCAD (MDT-UCR) project began in 2016, conceived as a research project of the University of Costa Rica, based on a partnership between the Civil Engineering School (EIC) and the National Laboratory of Testing Materials and Structural Models (LanammeUCR). The present article describes the database migration of the urban transportation demand model, from Emme2 to TransCAD, generated as a result of the Regional Urban Plan for the Great Metropolitan Area of Costa Rica (PRUGAM). The databases include the roads and transit networks, the transit system’s operational characteristics and the socioeconomic variables used for transportation demand modeling. Each step of the demand model migration process is described. This article covers the methodology used for exporting data generated in Emme2 to TransCAD and the considerations used for validating both the databases’ migration process and the results obtained from the migrated urban transportation demand model in TransCAD. The main conclusion drawn from the migration process is that, even though some changes in the structure of the data had to be made, the urban transportation demand model was successfully migrated from Emme2 to TransCAD, without changes to its contents. The analytical methods included in TransCAD are similar to those used in Emme2, so the results obtained by the model were successfully replicated.